2005
DOI: 10.1109/tasc.2005.849995
|View full text |Cite
|
Sign up to set email alerts
|

Nanomagnetic Particles for SQUID-Based Magnetically Labeled Immunoassay

Abstract: With the increasing importance of SQUID-based magnetically labeled immunoassay, the study on the synthesis of controllable sizes of magnetic nanoparticles plays a role to promote the accuracy of the immunoassay. In this work, Fe 3 O 4 nano-particles coated with a suitable bio-probe (biotin) are synthesized through chemical co-precipitation process to probe the bio-target (avidin). Through the synthesis developed here, the particle hydrodynamic diameter can be adjusted from 30 to 90 nm, which provide candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The details of these chemical reactions for binding biotin to dextran have been reported in Ref. [15]. Finally, through magnetic separation, the unbound probing single-strand DNAs were removed from the magnetic reagent, whose pH was around 7-8.…”
Section: Methodsmentioning
confidence: 99%
“…The details of these chemical reactions for binding biotin to dextran have been reported in Ref. [15]. Finally, through magnetic separation, the unbound probing single-strand DNAs were removed from the magnetic reagent, whose pH was around 7-8.…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] Briefly, a ferrite solution containing ferrous sulfate heptahydrate (FeSO 4 ⋅7H 2 O) and ferric chloride hexahydrate (FeCl 3 ⋅6H 2 O) in a stoichiometric ratio of 1:2 was mixed with an equal volume of aqueous dextran. Dextran was served as a surfactant for Fe 3 O 4 particles distributed in water because of its nontoxicity, hydrophilicity, and high affinity for biological macromolecules.…”
Section: Conjugation Of Cd133 Ab With Uspiomentioning
confidence: 99%
“…It has been shown technically that the magnetically labeled immunoassay has the merits of high sensitivity, 6 versatile diagnostic methods, [6][7][8][9] convenient processes, 7,8 and high accuracy for detecting biomarkers, and could potentially be used in the clinical setting. In fact, magnetic particles have been used in cell sorting for the detection of human leukocyte antigen B27, 10 and it has been shown that the performance of magnetic cell sorting is much better than that of flow cytometry.…”
Section: Introductionmentioning
confidence: 99%